1996
DOI: 10.1063/1.117024
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of diffuse photon-density wave interference in turbid media from time-resolved transmittance measurements

Abstract: We demonstrate an improved technique to precisely localize inhomogeneities in turbid media by means of reconstructing diffuse photon-density wave interference from time-resolved transmittance measurements applying the Fourier transform. This interference can also be obtained in the reverse mode, that is using a single source and combining the signals detected at several locations. This increases the collection efficiency and the possibility for postprocessing and allows one to evaluate the data from one measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Visual analysis of a second data set, provided by ART, suggested that a similar situation existed with that data. As such, the results shown for the known phantom are those at the (30,30,30) 4659 0.7352 (20,20,20) 2109 0.7362 (15,15,15) 1098 0.7409 (10,10,15) 578 0.7294 (10,10,10) 402 0.7404 minimum error point, while those shown for the second data set were chosen to be "underregularized" by a similar order of magnitude. Of course, critical to determining the utility of the interpolation is evaluation of the error introduced into the reconstructions.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual analysis of a second data set, provided by ART, suggested that a similar situation existed with that data. As such, the results shown for the known phantom are those at the (30,30,30) 4659 0.7352 (20,20,20) 2109 0.7362 (15,15,15) 1098 0.7409 (10,10,15) 578 0.7294 (10,10,10) 402 0.7404 minimum error point, while those shown for the second data set were chosen to be "underregularized" by a similar order of magnitude. Of course, critical to determining the utility of the interpolation is evaluation of the error introduced into the reconstructions.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In diffuse optical tomography (DOT), near-infrared light is introduced to the body from an array of sources on the surface and collected at a number of detectors as it exits [3,7,8,12,15,17,26,27]. The imaging problem consists of determining images of photon absorption and/or diffusion in the body from this measured photon fluence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is based on the use of dual-interfering sources 2,3 . In this configuration, two rfmodulated out-of-phase sources with the same strength illuminate the media.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. (15,16), it is shown that destructively interfering diffuse optical wave fields are used to detect light absorptive inhomogeneities. Similar to the principle of a Wheatstone bridge using a true zero, two modulated light sources of the same intensity but of opposing phases destructively interfere and create a line of null oscillations in between them.…”
Section: Introductionmentioning
confidence: 99%